ANALYSIS OF THE FINANCIAL PERFORMANCE OF COMPANIES LISTED ON THE INDONESIAN STOCK EXCHANGE (BEI) BEFORE AND DURING THE COVID-19 PANDEMIC - Mazliza Mazliza; Arum Kusumaningdyah Adiati (Proceedings of the 1st International Conference on Social Science (ICSS), 2023)
This research is a type of quantitative research with the aim of knowing the financial performance conditions of companies listed on the Indonesia Stock Exchange before and during the Covid-19 pandemic. The samples used are companies listed on the Indonesian Stock Exchange for the 2019-2021 period and accessed via the official website of the Indonesian Stock Exchange at (www.idx.co.id). The research sample was selected using techniquespurposive sampling and a total of 592 companies that met the criteria were obtained and 1,776 financial report data were observed during the 2019-2021 period. The data used in this research is secondary data, while the data collection technique uses documentation techniques. The analytical methods used are descriptive statistical tests, normality tests and difference testsWilcoxon Signed Rank Test. Data testing is carried out using statistical calculations through the applicationStatistical Product Service and Solution (SPSS). The research results showed that there were 3 variables that experienced significant differences between before and during the Covid-19 pandemic in companies listed on the Indonesia Stock Exchange. These differences occur in the variables of liquidity, profitability and activity in the form ofcurrent ratio (CR), return on assets (LONG),total assets turnover (TATTOO). Meanwhile, the solvency variable is measured usingdebt to equity ratio (DER) there is no significant difference between before and during the Covid-19 pandemic